Description of the new subspecies Anophthalmus pretneri ceji (Coleoptera: Carabidae: Trechinae) from Slovenia - Vrezec, Al (Acta entomologica slovenica (Ljubljana), 2001)
The new subspecies Anophthalmus pretneri ceji ssp. n. is described from the cave Snežnica pod Korenom on Mt. Krvavec (Kamniško-Savinjske Alps, 1920 m a.) Some characteristics of the new taxon are compared with other subspecies of A. pretneri. Main diagnostic features of the new subspecies are:pore 1 in series umbilicata is above or at the level of pore 2, distinctlyangulate elytral shoulders and long aedeagus.
Keywords: Coleoptera; Ecosystem; Ekosistem; Hrošči; zoologija; zoology